SCIENCE LEARNING MEDIA: ANALYSIS OF UTILIZATION IN CLASS V MI AL MUBAROK - Hikmatul Immayanti; Putri Ika Cahyani; Nurhaningtyas Agustin (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
Learning media are tools or intermediaries used by teachers to channel information to students so that learning objectives are achieved. If we look at the facts on the ground, learning media has its own advantages and challenges in improving the quality of learning, especially at MI. Teachers are required to carry out learning using media, but on the other hand, they face many obstacles such as inadequate facilities and infrastructure. This condition makes teachers have to rack their brains with their abilities and creativity together with students to create alternative media so that the use of media is appropriate and not a barrier to learning. This research aims to analyze the use of learning media and the problems of using science learning media in class V as well as efforts to overcome these problems. This research was conducted at MI Al Mubarok Semanding. This research uses a qualitative approach with a case study type of research. Namely focused on learning media analysis. Data collection techniques include observation, interviews and documentation. The results of this research show that teachers are able to face the challenges of technological limitations by creating alternative media with students. However, schools are also trying to fulfill the provision of technology-based media by running a one day one coin program so that learning is more effective and efficient.